DIROSATU AT-TANASH FII QISHOH QOSHIROH "KANZU ASY-SYAMARDAL" LI KAMIL KILANI WA HIKAYAT "JAUDAR BIN 'UMAR AT-TAJIR MA'A AKHOWAIHI" FII ALFI LAILAH WA LAILATIN - Zaujah Rodliyah Dzikrunastiti; Halimi Halimi; Muhammad Majed Al-Dakhiel (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2022)
Intertextual studies are efforts made to find certain aspects contained in the previous works and the works that follow. The similarities in some of these literary works are not part of plagiarism because the author develops their works in style. This research focuses on the intrinsic elements in the short story "The Syamardal Treasure" by Kamel Kilani and the story of "Jodar bin Omar, The Merchant with His Two Brothers" in The Thousand and One Night, and intertextual form between the two. The methods used in this research are a qualitative descriptive method, reading and note-taking techniques to collect data, data reduction, data display, and conclusion drawing for analyzing data. The results of this study reveal that the intrinsic elements in the short story "The Syamardal Treasure" by Kamel Kilani and the story of "Jodar bin Omar, The Merchant with His Two Brothers" in The Thousand and One Night are in the form of themes, storylines, characters and characteristics, settings, point of view, and mandate. In addition, there are also many general similarities and differences found in its intrinsic elements, such as similarities in storylines, characters and characteristics, settings, point of view, and mandate; differences in themes and titles.